Mn3Ag(1-x)Cu(x)N antiperovskite thin films with ultra-low temperature coefficient of resistance. (10th February 2022) - Lukose, Cecil Cherian; Zoppi, Guillaume; Birkett, Martin
Highlights: First report on the reactive sputter deposition and post-deposition heat treatment of Mn3 Ag(1- x ) Cu( x ) N thin films for ultra-low TCR application. Increasing Cu doping concentration in Mn3 Ag(1- x ) Cu( x ) N controls stabilization of the manganese oxide upper surface layer. The extent of upper surface oxidation and crystallization of the underlying thin film are competing events to fine tune the electrical properties. Optimising the post-deposition heat treatment temperature results in TCR values better than ±5 ppm/°C and resistance stability of less than 1%. Abstract: We demonstrate the first successful attempt to partially substitute Cu into the Mn3 AgN-antiperovskite system to form Mn3 Ag(1- x ) Cu( x ) N thin films with an ultra-low temperature coefficient of resistance (TCR) for fabrication of ultra-precise passive components. Films were grown by reactive magnetron sputtering on alumina and glass substrates and were found to be amorphous in nature with highly negative TCR of -233 to -351 ppm/°C in their as-grown state. Increasing Cu alloying from x =0 to 1, resulted in increased sheet resistance, a negative shift of TCR and a change of grain morphology from spherical to elongated. Post-deposition heat treatment at 300-375 °C, resulted in a positive shift of TCR and an ultra-low TCR of -4.66 ppm/°C for films with x =0.6. The heat treatment induces grain growth, surface roughness and the formation of a manganese oxide upper surface layer up until temperatures of 350 °C, after which surface oxidation begins to dominate. The growth rate of the surface layer is controlled by the Cu concentration and heat treatment temperature, which both play a central role in the development of these novel ultra-low TCR Mn3 Ag(1- x ) Cu( x ) N thin film structures. Graphical abstract: Image, graphical abstract